Airport Noise: From Monthly Variability to the Impact of Technology Uptake on Long-Term Projections - Einicke, Karina (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2025)
The surrounding communities of Dublin Airport are experiencing increasing noise due to increasing air traffic. Aircraft noise is a significant environmental issue, with substantial implications for public health and quality of life, contributing to annoyance and increasing the risk of health problems, including cardiovascular diseases. Consequently, it is essential to analyze current and future noise exposure in terms of population and area exposure, and to lay focus on noise mitigation measures to reduce negative health effects. This thesis examines the short-term and long-term airport noise at Dublin Airport, exploring monthly fluctuations and the integration of future aircraft concepts. Currently, environmental noise, including airport noise, is mapped every five years under Environmental Noise Directive (END), which mandates the production of annual noise contours. However, this thesis demonstrates that conventional annual noise maps fail to capture substantial monthly fluctuations in noise exposure. In some cases, the maximum monthly change in area exposure reaches up to 100 % a level of variation that annual averages are incapable of representing. To address this gap, the thesis introduces maximum monthly change in area exposure as a novel metric to quantify and visualize these significant temporal dynamics. To address a critical aspect of airport noise communication related to long-term forecasting for improved planning, including land use management and the protection of communities near airports, this thesis presents noise level projections through to the year 2050. The forecasts for 2030, 2040, and 2050 combine expected increases in air traffic with technology uptake, including the introduction of quieter generation 2 and 3 aircraft. From 2023 to 2030, the area exposed to noise levels of Lden= 45 dB(A) is projected to increase from 171.48 km2 to 217.32 km2. In the 2040 scenario, despite an increase in air traffic, it is possible to reduce the exposed area to 199.30 km2, representing a decrease of 8.29 % compared to 2030. The 2050 noise predictions are based on simulated noise data for future aircraft concepts, specifically the Blended Wing Body aircraft, as a proxy for emerging technologies. Therefore, Noise-Power-Distance (NPD) data was generated for integration into the noise model. The study further evaluates Dublin Airport's communication strategy regarding noise exposure and offers recommendations for improving public engagement and policymaker responses to evolving noise trends. However, even with the introduction of future aircraft concepts, the exposed area increases to 214.10 km2, which corresponds to an increase of 24.87 % compared to 2023, while the total number of flights increases by 47 %. The findings highlight significant gaps in current noise forecasting and communication, stressing the need for more detailed, and dynamic models that account for seasonal and monthly noise variations. This thesis concludes with policy recommendations for better noise mitigation, land-use planning, and the adoption of quieter aircraft technologies to reduce long-term airport noise exposure.
APPROVED
Keywords: airport noise; aircraft noise; noise mapping; airport noise mapping; noise power distance; noise data; future aircraft concept; generation 3; new aircraft concept; aircraft fleet renewal; aircraft technology uptake; air traffic increase; monthly noise fluctuation; annual noise map; airport noise forecast; airport noise prediction; aircraft noise prediction